Peran Serikat Pekerja dalam Hal Perselisihan Hubungan Kerja yang Berdampak pada Pemutusan Hubungan Kerja - Enggartiasti Sherly Anggraini (Syntax Corporation Indonesia, 2023)
In every company, of course, always strive to create a cooperative and comfortable work environment for each worker. This study aims to analyze the role of trade unions in overcoming labor relations disputes that can have an impact on termination of employment. The research method raised in this study is Normative research. Normative Law Research is legal research conducted by examining library materials or secondary data